2017
DOI: 10.3892/mmr.2017.6482
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Tim-3 expression on peripheral NK cells is correlated with pathologic TNM staging in colorectal cancer

Abstract: Previous research has indicated that T cell immunoglobulin and mucin domain 3 (Tim-3) serves an important regulatory role in lymphocytes and in several cancers. However, the association between Tim‑3 expression on various lymphocyte subsets and human colorectal cancer (CRC) has not been elucidated. The present study aimed to characterize Tim‑3 expression on peripheral lymphocytes, including cluster of differentiation CD3+CD56‑ T cells, CD3‑CD56+ natural killer (NK) cells and CD3+CD56+ natural killer T (NKT) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
(33 reference statements)
0
28
0
Order By: Relevance
“…Here, as well, blocking TIM-3 with antibodies increased NK cell cytotoxicity and cytokine secretion. Additional recent studies identified TIM-3 expression as a marker of NK cell dysfunction and disease severity in colorectal cancer, esophageal cancer, endometrial cancer, and bladder cancer (96,(98)(99)(100)(101). Interestingly, TIM-3 engagement was initially shown to increase the expression of IFN-γ by NK cells in response to galectin-9, the β-galactoside binding lectin (123).…”
Section: Tim-3mentioning
confidence: 99%
“…Here, as well, blocking TIM-3 with antibodies increased NK cell cytotoxicity and cytokine secretion. Additional recent studies identified TIM-3 expression as a marker of NK cell dysfunction and disease severity in colorectal cancer, esophageal cancer, endometrial cancer, and bladder cancer (96,(98)(99)(100)(101). Interestingly, TIM-3 engagement was initially shown to increase the expression of IFN-γ by NK cells in response to galectin-9, the β-galactoside binding lectin (123).…”
Section: Tim-3mentioning
confidence: 99%
“…Notably, alterations in circulating NK cells frequency, phenotype and function have also been found in tumour patients and have been associated with the clinical outcome . So far, the analysis of peripheral blood NK cells in solid tumours patients showed an association between a suppressed functionally impaired NK cells phenotype and poor prognosis.…”
Section: Natural Killer Cells and Melanoma Immunotherapymentioning
confidence: 99%
“…Since Tim‐3 expression is induced by activating cytokines and marks the most cytotoxic NK cell subset with the highest IFN‐γ production, it could act by limiting the duration and magnitude of NK cell responses, thus preventing chronic activation . However, even if Tim‐3 expression on NK cells is usually linked to exhaustion and impaired function, such association may be tumour‐dependent, since colorectal cancer patients show reduced frequencies of Tim‐3 + NK cells negatively correlating with disease stage and increasing after tumour resection …”
Section: Natural Killer Cells and Melanoma Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations